Synthesis, Characterization and Electrochemical Properties of Polymers Based on Dithienothiophene and Bithiazole. Issue 9 (9th June 2020) - Dikcal, Fatma; Topal, Sebahat; Unal, Murat; Ozturk, Turan
Abstract: Conjugated polymers are promising cost‐effective, lightweight, and flexible electrode materials. 3, 5‐Dinonyl‐2, 6‐di(thiophene‐2‐yl)dithieno[3, 2‐b : 2′, 3′d]thiophene (M1 ) as a donor and 4, 4′‐dinonyl‐5, 5′‐di(thiophen‐2‐yl)‐2, 2′‐bithiazole (M2 ) as an acceptor were synthesized and their polymers poly(3, 5‐dinonyl‐2, 6‐di(thiophene‐2‐yl)dithieno[3, 2 b : 2′, 3′‐d]thiophene) (P1 ) and poly(4, 4′‐dinonyl‐5, 5′‐di(thiophen‐2‐yl)‐2, 2′‐bithiazole) (P2 ) were obtained via electropolymerization on ITO/glass electrode surface in ACN : DCM (1 : 3 v/v) solution, containing 0.1 M tetrabutylammonium hexafluorophosphate (TBAPF6 ). Then, a third polymer as a co‐polymer (P3 ) was synthesized through electropolymerization of a mixture of the monomers M1 and M2 in 1 : 1 ratio. All the polymers were characterized by UV‐Vis, CV and CV‐UV measurements. Moreover, capacitor properties of the polymers by potentiostatic electrochemical impedance spectroscopy (EIS) was performed. The polymers P1, P2 and P3 exhibited absorptions at 456, 453 and 519 nm in neutral state and their optical band gaps were determined to be 2.17, 2.53 and 1.95 eV, respectivetly. EIS measurements indicated that P3 had the highest current density, having lower resistance. Abstract : Electropolymerization of a mixture of dithienothiophene and bithiazole has been realized and electrochemical properties have been explained.